Analysis of The Role of Organizational Citizenship Behavior to Optimize Work Discipline - Rizki Dwi Ariyanto; Mulyono (Journal of Management Research and Studies, 2023)
This study aims to determine the effect of Public Service Motivation on Work Discipline through strengthening Organizational Citizenship Behavior. The population in this study were all teachers who worked at Purwantoro Elementary School, Malang City. The sampling technique used in this research is Nonprobability Sampling with a total of 91 respondents. And the data is processed through Smart Partial Least Square (PLS) software. The results of this study indicate that public service motivation, which is still low, has not been able to contribute to improving teacher performance at SDN Purwantoro, Malang City. Likewise, organizational citizenship behavior (OCB) is getting better, it will be able to contribute to teacher work discipline. It was also found in this study that the better the organizational citizenship behavior (OCB), the more it would contribute to the teacher's work discipline. As well as high or increasing public service motivation, accompanied by a good role of organizational citizenship behavior, then work discipline will be better.